2017
DOI: 10.2136/vzj2017.04.0074
|View full text |Cite
|
Sign up to set email alerts
|

Water Balance Dynamics during Ten Years of Ecological Development at Chicken Creek Catchment

Abstract: Core Ideas Water balance was calculated for the constructed catchment Chicken Creek. Influence of abiotic and biotic factors feedback mechanisms on the hydrology was determined. Different phases were derived during the development of the ecohydrological system. Difficulties in quantitatively closing the water balance of catchments arise when upscaling point measurements and from insufficient knowledge of the physical boundaries, inner structure, and storage volumes of natural catchments. In addition, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Most studies have shown that lateral subsurface flow occurs either because of temporary saturation above an impeding layer or because the water table rises into a more permeable layer near the surface (Weiler et al., 2005). Soil development leads to an increase in fine particles due to physical weathering (He & Tang, 2008; Mavris et al., 2010; Righi et al., 1999) and chemical weathering (i.e., clay formation; Crocker & Dickson, 1957; Román‐Sánchez et al., 2021; Schaaf et al., 2017; Young et al., 2004). Illuviation of this fine‐textured material leads to a lower permeability layer that promotes ponding and lateral SSF (e.g., Dahlke et al., 2012; Lohse & Dietrich, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that lateral subsurface flow occurs either because of temporary saturation above an impeding layer or because the water table rises into a more permeable layer near the surface (Weiler et al., 2005). Soil development leads to an increase in fine particles due to physical weathering (He & Tang, 2008; Mavris et al., 2010; Righi et al., 1999) and chemical weathering (i.e., clay formation; Crocker & Dickson, 1957; Román‐Sánchez et al., 2021; Schaaf et al., 2017; Young et al., 2004). Illuviation of this fine‐textured material leads to a lower permeability layer that promotes ponding and lateral SSF (e.g., Dahlke et al., 2012; Lohse & Dietrich, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This low influence of abiotic habitat conditions implies that functionality during plant succession was driven by other filter processes, possibly soil humidity. After the emergence of the first woody plants in 2007 increasing habitat differentiation accentuated the roles of microclimate and shade as additional strong filter agents (Schaaf et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The catchment has been equipped with wide variety of sensors to monitor the spatiotemporal variability of meteorological, hydrological, ecological and soil attributes (Schaaf et al . ). Figure demonstrates an aerial photo of the test site along with the transect.…”
Section: Methodsmentioning
confidence: 97%
“…On ecosystem development, Chicken Creek was constructed in the Lusatian lignite district of the Brandenburg, Germany from 2004 to 2005. The catchment has been equipped with wide variety of sensors to monitor the spatiotemporal variability of meteorological, hydrological, ecological and soil attributes (Schaaf et al 2017). Figure 1 demonstrates an aerial photo of the test site along with the transect.…”
Section: Study Area and Measurementsmentioning
confidence: 99%